Marital Satisfaction and Related Factors among Married Women - Nouri 1, Mahnaz; Hosseini Kebria 2, Mohadeseh; Ahmadianfar 2, Frouzan; Khosravi 3, Ahmad; Amiri 4*, Mohammad - (Shahroud Journal of Medical Sciences, 2019)
background: Marital satisfaction is one of the factors affecting life which influences the permanence and durability of the married life. This study aimed at assessing marital satisfaction and some of its associated factors.Methods: In this cross-sectional study, 500 married women who referred to health care centers and obstetrics and gynecology clinics in 2017 were evaluated using the Enrich Marital Satisfaction Scale. The collected data were analyzed using Chi-square and one-way analysis of variance.Results: The mean score of marital satisfaction was 118.33±22.06. Based on the marital satisfaction score, 6 (1.2%) of the participants had low marital satisfaction; 132 (26.4%) had moderate marital satisfaction; 281 (56.2%) had a high marital satisfaction and 81 (16.2%) had very high marital satisfaction. Significant relationships were observed between marital satisfaction and age (P=0.005), length of marriage (P=0.001), age of spouse (P =0.003), number of children (P=0.003), age at the first marriage (0.024), woman’s education and husband's education (P=0.001), income (P=0.001), pregnancy experience (P=0.001) and childbirth experience (P=0.001). However, there was no significant relationship between marital satisfaction and job, husband's job and place of residence (P≥0.005).Conclusions: Since marital satisfaction was found to be associated with age, education, age of the spouse, length of marriage, number of children, income, pregnancy experience and childbirth experience, establishment of sexual counseling clinics in health care centers and providing premarital counseling and counseling on sexual issues for the couples can help them improve their marital satisfaction.